Log in to add a comment

## Answers

**Solution**⇒

⇒ 4 - 5 = 3

------- --------- -----

z - 1 z + 2 z

⇒ 4z + 8 - (5z - 5) = 3

--------------------- ----

z² - z + 2z -2 z

⇒4z - 5z + 8 + 5 = 3

------------------ -----

z² + z - 2 z

⇒(-z + 13)z = 3z² + 3z - 6

⇒-z² + 13z = 3z² + 3z - 6

⇒3z² + 3z - 6 + z² - 13z = 0

⇒4² - 10z - 6 = 0

**Dividing whole equation by 2**

⇒2z² - 5z - 3=0

⇒2z² - 6z + z - 3=0

⇒2z(z - 3) + 1(z - 3) = 0

⇒(2z + 1) (z - 3) = 0

⇒2z + 1 = 0

**OR**z - 3=0

2z = -1 z = 3

z = -1/2

**Therfore,**

**z = -1/2 OR z = 3**